ChemInform Abstract: A Novel Triphosphoramidite Ligand for Highly Regioselective Linear Hydroformylation of Terminal and Internal Olefins. Issue 31 (11th July 2013) - Chen, Caiyou; Qiao, Yu; Geng, Huiling; Zhang, Xumu
Abstract Ligand (I) gives good results in the title reaction.